Evaluation of Mango Byproduct Extracts as Antioxidant Against Pb-Acetate-Induced Oxidative Stress and Genotoxicity in Mice - Makawy Aida I. El; Ashoush Ihab S.; Abd-Elmoneim Omaima M. (Polish Journal of Food and Nutrition Sciences)
The antioxidant and antiproliferative properties of mango by-products were investigated. This study was carried out to evaluate the protective role of mango peel or kernel defatted extracts against Pb-acetate adverse effects on oxidant/antioxidant status, liver dysfunction biomarkers, histopathological changes and genotoxicity in male mice. Total phenolic content and antioxidant activity of both extracts were evaluated. Two doses of both extracts (50 and 100 mg/kg) were used to evaluate their role against the toxicity of Pb-acetate (500 ppm). Mice given mango extracts with Pb-acetate had significantly lower plasma MDA, AST and ALT and higher glutathione than mice given Pb-acetate alone. Mango extracts prevented the histopathological changes in liver induced by Pb-acetate and decreased the cytotoxicity of lead by increasing the ratio of PCE/NCE. Mango extract treatment reduced the DNA damage induced by Pb-acetate in liver as demonstrated by a reduction in micronuclei and decrease in tail length, tail DNA% and Olive tail moment. It can be concluded that mango by-product extracts have potential to protect from oxidative stress and genotoxicity of lead.